Solidarities of citizenship - Stevens, Jacqueline (Frontiers in Political Science, 2023)
This essay contrasts the trajectory of Engin Isin’s work since Being Political (2002) with a very different intellectual path pursued among scholars of a younger generation. Isin moves away from his initial critiques of citizenship and ten years later proposes "citizenship without frontiers" a way of understanding emancipatory interventions of active citizens in opposition to state violence. During this same time frame other political theorists began to reject “citizenship” entirely. Whereas Isin’s ouevre since Being Political incorporates the principles of creativity and resistance of “being political” into a more expansive concept of “citizenship,” other theorists began denouncing citizenship as of a piece with colonialism, capitalism, and neoliberalism. Such reactions expressly rejected efforts to recuperate citizenship for causes that oppose domination and oppression. This essay analyzes the anti-citizenship claims by Glen Coulthard (2014) and Brandzel (2016) through the lens of Isin's work, focusing in particular on competing views on nativism, Indigeneity, and nationality. The Conclusion considers recent examples of activist citizens and citizens without frontiers pursuing political solidarities along the lines Isin proposes.